Novel existence results for sequential Caputo FDE with antiperiodic and integral boundary conditions - Abdolhadi Dabbaghian; Rahmat Darzi (Mathematics and Computational Sciences, 2023)
In this paper, by assuming certain assumptions, we study a novel class of sequential Caputo fractional differential equations (FDE) Consist of antiperiodic and Riemann-Liouville (R-L) fractional integral boundary conditions. The existence and uniqueness of the solution to the proposed class of problems utilizing the fixed point theory and some new equalities of norm form are investigated. At the end of the paper, two specific examples of the study results are offered to demonstrate its performance and effectiveness.